Democracy in Paradise - Joyau, Marc (Victoria University of Wellington Law Review, 2004)
This article explores the theme of democracy in French Polynesia. The author discusses questions which have most often been touched upon in the discussions which relate to the adoption of the new constitutional statute, and the place of democracy in relation to the designation of local government organisations.